Malaysian Private Entity Reporting Standard (MPERS) For Small Medium Enterprises In Malaysia: Value Adding Or Additional Pain? - Nurul Nazlia Jamil; Nathasa Mazna Ramli; Ainulashikin Marzuki; Nurul Nadiah Ahmad (Usuli Faqih Research Centre PLT., 2024)
Vol 7 No 1 (Page: 16-28)